2021
DOI: 10.3143/geriatrics.58.591
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in activity and its related factors under COVID-19 crisis in community-dwelling older people

Abstract: Aim: To prevent the transmission of the novel coronavirus and stop its spread, a state of emergency was declared from April to May 2020. People were encouraged to refrain from outings and reduce their contact with people. The purpose of this study was to examine the subjective changes in the amount of activity under COVID-19 crisis among the elderly and the factors related to this decrease in activity. Methods: This study was part of the SONIC study, an ongoing prospective cohort study targeting community dwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…A total of 269 participants living in Itami and Asago responded to the appropriate questionnaires of this study (response rate: 54.2%). [20]. Among them, the participants who had not been diagnosed with "major sarcopenia" in the previous survey of 2019 (n = 252) were included in the study.…”
Section: Participantsmentioning
confidence: 99%
“…A total of 269 participants living in Itami and Asago responded to the appropriate questionnaires of this study (response rate: 54.2%). [20]. Among them, the participants who had not been diagnosed with "major sarcopenia" in the previous survey of 2019 (n = 252) were included in the study.…”
Section: Participantsmentioning
confidence: 99%
“…Godai et al reported that people living in rural areas had a higher amount of activity than those living in urban areas. 28 Differences in lifestyle and behavior between urban and rural areas might have influenced the onset of anemia. However, further research is required to confirm the relationship between activity level and anemia.…”
Section: Discussionmentioning
confidence: 99%